Merdeka Curriculum: Perceptions of Physical Education Teachers, Sports and Health - Ade Setya Nugraha; Septian Raibowo; Yahya Eko Nopiyanto; Miftah Fajrin Rahmi (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
This research aims to determine the perceptions of physical education teachers, sports and health towards learning media in state high schools throughout the city of Bengkulu. This type of research is descriptive research with a qualitative approach using survey methods. The research subjects were 20 Public High School Physical Education teachers in Bengkulu City using purposive sampling. Using questionnaire, interview and documentation data collection techniques. Data analysis used in this research is data reduction, data display, conclusions/verification. The results of the questionnaire for 20 respondents got an average score of 74% in the good category and from the results of the interviews they got an average score of 62% so that teachers' perceptions of Merdeka learning in public high schools throughout the city of Bengkulu were in the good category.